Penjadualan Produksi Melalui Sistem Produksi Just In Time dengan Kaban Guna Memenuhi Permintaan - Eti Kristinawati (Jurnal Teknik Industri, 2001)
JustI n Timep roductions ystemis a productions ystemw hichp roducea productw hent heyare neededa nd a fit numbero f productt o achievet he consument'sd emand.T o make theproductionp rocessru n well so it mustb e made a plana nd scheduleo f goodp roductionp rocessrangkingw hich is approachw ith the demandc ondition.CV. SugrhW arasi s a furniturec ompanyw hich has a demando f producti ncreaseT. hisproblemw ill maket he companyh ast roublet o achievei t. JIT productions ystemw ith using ascheduleo f productiona nd kanbanb ecomea problems olvinga lternetiveto solvet he customerdemandp roblemF. rom the analysisw e shownt hat usingJ IT problems ystemc anr educeth e backordero fproductr esult.T hep rofit canb e reachedb eforei mplemenJt IT is Rp 253.236.000,0a0n dafteri mplemenJt IT isRp 289.803.000,0s0o t hati ncreasea bout Rp 36.567.000,O0or1 4.44yo.